2022
DOI: 10.1016/j.jhsa.2021.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Return to Usual Work Following an Ulnar Shortening Osteotomy: A Sample of 111 Patients

Abstract: §k on behalf of the Hand-Wrist Study Group, Brigitte Van der Heijden, PhD, MD*{ Purpose The primary aim of this study was to analyze the median time until patients performed their usual work following an ulnar shortening osteotomy (USO). The secondary aim was to identify factors influencing the median time until return to their usual work.Methods We used a retrospective cohort of patients with ongoing data collection from our institution in the Netherlands. Patients with paid employment who underwent USO were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…While all USOs were performed at the level of the diaphysis using an oblique cut, there was variation in the manner of the osteotomy (freehand versus specific USO devices) and the type and position of the fixation plate, which may have influenced the outcomes during follow-up. Although previous research did not find a difference in pain relief or return to work between freehand USO and specific USO devices [ 32 , 33 ]. Fourth, some patients underwent concomitant surgery during the USO, which could have induced some co-treatment bias.…”
Section: Discussionmentioning
confidence: 89%
“…While all USOs were performed at the level of the diaphysis using an oblique cut, there was variation in the manner of the osteotomy (freehand versus specific USO devices) and the type and position of the fixation plate, which may have influenced the outcomes during follow-up. Although previous research did not find a difference in pain relief or return to work between freehand USO and specific USO devices [ 32 , 33 ]. Fourth, some patients underwent concomitant surgery during the USO, which could have induced some co-treatment bias.…”
Section: Discussionmentioning
confidence: 89%
“…However, the time until RTW is similar to that for other major wrist surgeries in our sample, such as open triangular fibrocartilage complex repair and ulna shortening osteotomy. 18,26 Previous studies have shown that grip strength of 75%e91% of the contralateral side can be expected and a ROM arc of 72 e76 . 23,24 The present study enhances our knowledge by showing that although there is a reduction at 3 months, patients can be reassured that by 12 months, they will have regained almost 100% of their preoperative grip strength, although the operated side remained impaired compared with the unoperated hand (81% of unoperated hand).…”
Section: Discussionmentioning
confidence: 99%
“…Details on the RTW questionnaire and definitions have been described previously. 18 Patients completed their level of satisfaction with treatment results by email on a validated 5-point Likert scale. 19 A hand therapist measured the active wrist ROM and grip strength during consultation before, and at 3 and 12 months after surgery.…”
Section: Treatmentmentioning
confidence: 99%
“…30 We selected age, sex, occupational intensity, dominance, the duration of symptoms (in months), and MHQ scores at baseline as possible influencing factors of the RTW based on previously published literature. [20][21][22] Besides, the authors agreed upon adding hand comorbidity, diagnosis, and implant type as possible influencing factors specifically for patients following PIP joint arthroplasty. We evaluated the median times until RTW of all factor subgroups, and in the case of continuous variables, we categorized based on the median value.…”
Section: Methodsmentioning
confidence: 99%
“…Return to work studies have been performed for other hand disorders, and injuries and several prognostic factors, such as sex, type of work, and the amount of postoperative pain, for RTW were found. [18][19][20][21] For instance, among patients undergoing surgical treatment for trapeziometacarpal osteoarthritis, the physical occupational intensity, surgery on the dominant hand, and better Michigan Hand Outcomes Questionnaire (MHQ) work score and hand function score of the opposite hand preoperatively led to a shorter time until patients returned to work. 22 Which factors are of importance for patients' RTW following PIP joint arthroplasty for osteoarthritis is unknown.…”
Section: Introductionmentioning
confidence: 99%